THE PARADIGM OF THEO-ANTHROPO-COSMOCENTRISM: REPOSITION OF THE CLUSTER OF NON-ISLAMIC STUDIES IN INDONESIAN STATE ISLAMIC UNIVERSITIES - Toto Suharto (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
State Islamic Universities (UIN) in Indonesia nowadays has developed their study courses by opening the faculty of social science and humanities and the faculty of the natural science. This development is constitutionally “has gone beyond” scientific mandate of UIN, which only had the authority to execute the education in the cluster of religious sciences. Applying the approach of philosiphy of knowledge, this paper tried to commit the reposition the sciences of non Islamic studies cluster in UIN so that there is no gap between the two clusters, by offering the application of the paradigm of theo-antropo-cosmosentrism. Applying content analysis on texts related to the theme of the study, this paper offered the integration model of "Triangle of Science" which is based on the paradigm of Theo-anhropo-cosmosentrism. This paradigm tried to integrate the paradigms of theocentrism, anthropocentrism and cosmocentrism.